Cross-border banking, bank market structures and market power: Theory and cross-country evidence - Franziksa Bremus (Deutsches Institut für Wirtschaftsforschung (DIW), 2013)
Patterns in cross-border banking have changed since the global financial crisis. This may affect domestic bank market structures and macroeconomic stability in the longer term. In this study, I theoretically and empirically analyze how different modes of cross-border banking impact bank concentration. I use a two- country general equilibrium model with heterogeneous banks developed by De Blas and Russ (2010) to grasp the effect of cross-border lending and foreign direct investment in the banking sector on bank market structures. The model suggests that both cross-border lending and bank FDI mitigate concentration. Empirical evidence from a linked micro-macro panel dataset of 18 OECD countries supports the theoretical predictions: higher volumes of bank FDI and of cross-border lending coincide with lower Herfindahl-indexes in bank credit markets.
Keywords: E44; F41; G21; 330; cross-border lending; bank foreign direct investment; bank market concentration; net interest margins